2000
DOI: 10.1016/s0194-5998(00)70137-9
|View full text |Cite
|
Sign up to set email alerts
|

Posturographic performance in patients with the potential for secondary gain

Abstract: Patients who have the potential for secondary gain are generally younger and have a much higher prevalence of normal audiovestibular evaluations and a much higher prevalence of nonorganic sway patterns on CDP. A high degree of clinical suspicion should be maintained when evaluating the dizzy patient who has a pending lawsuit, worker's compensation claim, or disability claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 14 publications
2
15
0
1
Order By: Relevance
“…Potential aggravation (simulation) of balance disorders can be excluded based on observations of patients during the clinical examination and on the measurement of SCPG. Similar conclusions were reached by Gianoli and Krempl during the use of dynamic posturography [15,16].…”
Section: Discussionsupporting
confidence: 85%
“…Potential aggravation (simulation) of balance disorders can be excluded based on observations of patients during the clinical examination and on the measurement of SCPG. Similar conclusions were reached by Gianoli and Krempl during the use of dynamic posturography [15,16].…”
Section: Discussionsupporting
confidence: 85%
“…Balance performance, measured by computerized posturography [8,14,16,21] or functional balance tests, such as timed one-leg-stance, forward reach [19] and timed upand-go [9], has been examined in relation to perceived handicap in patients with dizziness. In previous studies, patients with dizziness were treated as a homogenous group, and conflicting findings were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that balance performance, when measured quantitatively using laboratory or clinical testing, does not necessarily correspond to the extent of handicap in patients with dizziness, with correlations ranging from weak to moderate [14,16,19,21]. Lack of synchrony between subjective complaints and clinical findings with respect to balance ability is common in patients with dizziness [3,8,10,24] and could explain, at least in part, the inconsistency in the level of correlation reported in previous studies. Thus, when evaluating how unsteadiness contributes to perceived handicap, both balance performance and perceived unsteadiness should be taken into consideration.…”
mentioning
confidence: 99%
“…The incentive for financial gain differs across Europe, depending on the local legal requirements to prove incapacitating balance problems after an automobile accident [Committee of European Assurances, 2004]. Thus it is important to judge whether patients with apparently debilitating balance problems are consciously mimicking a balance deficit, especially when there is a possibility of financial gain [Binder and Rohling, 1996;Gianoli et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The 3 formulas of Cevette et al [1995] produced the best results; 88% of the malingerers were correctly classified. Mallinson et al [2005] developed a new set of criteria to identify malingering patients which included those of Cevette et al [1995], Gianoli et al [2000], and Goebel et al [1997]. The new criteria which differed were: scoring a patient's performance when the patient is unaware of being assessed, a rhythmic sway pattern throughout all tasks, and finally exaggerated or erratic responses which could not be reproduced.…”
Section: Introductionmentioning
confidence: 99%